Production Barriers and Business Development of Pagatan Woven Fabric In Tanah Bumbu Regency - Siti Nurhalizah; Mutiani Mutiani; M. Ridha Ilhami; Rusmaniah Rusmaniah; Raihanah Sari (Journal of Social Development, 2026)
This study aims to identify the obstacles faced in the production process and business development in the small-scale industrial sector, particularly traditional woven fabric businesses. In the context of local culture-based economic development, woven fabric businesses play a strategic role in preserving cultural heritage while improving community welfare. However, in practice, business operators often face various challenges that hinder smooth production and business expansion. This study employs a qualitative descriptive approach with data collection techniques including observation, in-depth interviews, and documentation. The results indicate that the main challenges in the production process include limited access to high-quality raw materials, a shortage of skilled labor, weather conditions, limited business capital, marketing issues, and a shortage of skilled labor. Business operators have also begun to apply technology in the production process to improve efficiency and consistency of results. Commitment to cultural preservation is maintained in every innovation undertaken. Support from local governments, financial institutions, and creative communities further strengthens the business development process. This study shows that with the right development strategies, traditional woven fabric businesses have great potential to grow sustainably and competitively in both local and national markets.